Sistemas de inclusões diferenciais governadas pelo p-Laplaciano - Pereira, Ana Claudia (2004)
In this work we proof, by compactness methods, a local and global existence result for p-laplacian diferential inclusions with p > 2. Most of relevant theorems we need are in this text, including Monotone and Multivalued Operators Theory.